Understanding IPv6 Adoption in Hybrid Education Infrastructures: Challenges, Benefits, and Future Directions - Pascoal, R.; Galego, Nuno (Social Science Research Network, 2025)
The transition from IPv4 to IPv6 is critical for hybrid education infrastructures that increasingly depend on reliable connectivity and advanced technologies. This paper examines the drivers, barriers, and future directions of IPv6 adoption in this context, using a literature-based analytical approach supported by case studies, training initiatives, and global deployment models. The findings reveal that although IPv6 offers substantial benefits, such as scalability, enhanced security, improved performance, and energy efficiency, its adoption is hindered by high infrastructure and transition costs, limited technical expertise, and fragmented regulatory frameworks. By integrating technical, organizational, and policy perspectives, the paper highlights inclusive strategies and phased deployment models that can mitigate disparities, particularly in underfunded regions, and concludes that embracing IPv6 is not merely a technical upgrade but a strategic imperative for fostering innovation, bridging the digital divide, and enabling sustainable, future-proof learning environments.